« Mauvaise fatigue » et contrôle de soi : une approche sociohistorique - Marc Loriol (Perspectives Interdisciplinaires sur le Travail et la Santé)
Tiredness at work has long been associated with wear and tear on the body, leading to loss of strength and death. However, very early in human history, some individuals were confronted with activities that, although not requiring significant physical effort, nevertheless implied unprecedented commitment and control. New pathological categories emerged, ranging from acedia to chronic fatigue syndrome, to give a socially recognized meaning to this new form of fatigue experienced by individuals who found it difficult to adapt to the new requirements, and often to convey a sense of normality. These different nosologic entities share some similarities (attempt to organize pathological tiredness, lack of a recognized physiological basement, proximity to the dominant social norms among patients, etc.), but they are also embedded in a social context, which allows for a social constructionist approach.